Urban Flood Modelling: A Geospatial Evaluation of Drainage Systems for Resilient City Planning in Lusaka - Penjani Hopkins Nyimbili; Mukuka Himunga Mulenga; Bwalya J. Kawimbe; Faustin A. S. Banda; Erastus Misheng’u Mwanaumo; Wellington Didibhuku Thwala (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This study presents a flood modelling approach aimed at enhancing planning strategies to mitigate flooding impacts in Lusaka City. By integrating factors such as slope, hydrostatic potential surface, and the built environment, a predictive flood model was developed. The methodology involved using Geographic Information System (GIS) techniques and digital elevation models (DEMs) to assess geological features and manmade structures. Precipitation patterns and water demand analyses aided in computing a hydrostatic potential surface through watershed delineation. The generated flood model produced comprehensive flood maps illustrating water drainage in Lusaka, identifying vulnerable areas using Multi-Criteria Decision Analysis (MCDA) techniques. Results highlight the complex interaction between geographical features and human infrastructure in flood dynamics. This study contributes to informing zoning policies and disaster response planning, aiming to reduce the impact of future flooding events.